Near‐Infrared Laser‐Triggered Nitric Oxide Nanogenerators for the Reversal of Multidrug Resistance in Cancer. (15th February 2017) - Guo, Ranran; Tian, Ye; Wang, Yajun; Yang, Wuli
Abstract : The potential therapeutic implications of nitric oxide (NO) for diverse diseases have been under consideration for years; however, the development of precisely controllable NO generation system with potential for clinical application has remained elusive. Herein, intelligent near‐infrared (NIR) laser‐triggered NO nanogenerators for the treatment of multidrug‐resistant (MDR) cancer are fabricated by integrating photothermal agents and heat‐sensitive NO donors into a single nanoparticle. Such nanogenerators can absorb 808 nm NIR photons and convert them into ample heat to trigger NO release. The generated NO molecules are demonstrated to successfully achieve multidrug‐resistance reversal by inhibiting the expression of P‐glycol protein. Consequently, the intracellular accumulation of doxorubicin is effectively increased, resulting in high toxicity to MDR cancer cells in vitro. By virtue of surface modification with targeting ligands, these nanoparticles are able to selectively accumulate in tumor tissue. The therapeutic effects of the nanogenerators are validated in a humanized MDR cancer model. The in vivo experiment indicates that the nanoparticles possess excellent tumor suppression functionality with few side effects upon NIR laser exposure. Therefore, this novel photothermal conversion‐based NO‐releasing platform is expected to be a potential alternative to clinical MDR cancer treatment and may provide insights with regard to other NO‐relevant medical treatments. Abstract : Near‐infrared laser‐triggered nitric oxide (NO) nanogenerators are prepared by combining photothermal agents with heat‐sensitive NO donors. NO release is realized via the conversion of light to heat, and excellent controllability is achieved in aqueous solution and multidrug‐resistant (MDR) cancer cells under near‐infrared laser irradiation. Furthermore, the proposed NO‐releasing platform can successfully induce multidrug‐resistance reversal and tumor inhibition in a humanized MDR cancer model.